Об оптимизации методики ретроспективной оценки динамики размеров тела представителей Pelophylax esculentus complex (Amphibia, Ranidae) при помощи скелетохронологии - Усова, Е.Е.; Шабанов, Д.А. (Zoocenosis-2009. Біорізноманіття та роль тварин в екосистемах. –Дніпропетровськ, ДНУ, 2009)
Enhancing methods of retrospective estimation of the body size dynamics in Pelophylax esculentus complex (Amphibia, Ranidae) through the use of skeletochronology
Keywords: Pelophylax esculentus complex; Скелетохронология